To His Excellency Horatio Sharpe, Esq ; governor and commander in chief in and over the province of Maryland: the humble address of the House of Delegates - Sharpe, Horatio, 1718-1790 (Printed and sold by Jonas Green, printer to the province, 1761)
Address of the House of Delegates to Governor Sharper's following the King George II's death in 1760 and the succession of King George III.